Plant growth-promoting rhizobacteria: Salt stress alleviators to improve crop productivity for sustainable agriculture development - Kumawat, Kailash Chand; Sharma, Barkha; Nagpal, Sharon; Kumar, Ajay; Tiwari, Shalini; Nair, Ramakrishnan Madhavan (Frontiers in Plant Science, 2023)
Soil salinity, a growing issue worldwide, is a detrimental consequence of ever-changing climate which has highlighted and worsened the conditions associated with damaged soil quality, reduced agricultural production, and decreasing land areas, thus, quavering national economy. In this review, halo-tolerant plant growth promoting rhizo-microbiomes (PGPRs) are evaluated in the salinity affected agriculture as they serve as excellent agents in controlling various biotic-abiotic stresses and help in augmentation of crop productivity. Integrated efforts of these effective microbes lighten the load of agro-chemicals on the environment meanwhile managing the nutrient availability. PGPR assisted modern agriculture practices has emerged as a green strategy to benefit the sustainable farming without compromising the crop yield under salinity as well as salinity affected supplementary stresses including increased temperature, drought, salinity and potential invasive plant pathogenicity. PGPRs as bio-inoculants impart induced systemic tolerance (IST) to plants by the production of volatile organic compounds (VOCs), antioxidant, osmolytes, extracellular polymeric substances (EPS), phytohormones and ACC-deaminase and recuperation of nutritional status and ionic homeostasis. Regulation of PGPR induced signaling pathways such as MAPK and CDPK assist in salinity stress alleviation. The “Next Gen Agriculture” comprises of application of designer crop microbiomes through gene editing tools for instance CRISPR, engineering of the metabolic pathways of the microbes so as to gain maximum plant resistance. The utilization of omics technologies over the traditional approaches can fulfill the criteria required to increase crop yields in a sustainable manner for feeding the burgeoning population and augment the plant adaptability under climate change conditions ultimately leading to improved vitality. Furthermore, the constraints such as crop specificity issue of PGPR, lack of acceptance by farmers and legal regulatory aspects have been acknowledged while also discussing the future trends for product commercialization with the view of the changing climate.